Risky sexual behavior and family communication in adolescents of 3rd, 4th and 5th year of the secondary level of an I.E. state of the city of Iquitos - Gamboa Pumazoncco, Keshia (2020)
Objective: to determine the association between risky sexual behavior and family communicationin adolescents of 3rd, 4th and 5th year of the secondary level of a state I.E. of the city of Iquitos.Methodology: non-experimental design, cross-sectional and correlational scope. It was carried out in agroup of 500 adolescents between 13 and 19 years old. The instruments used were the questionnaireSexual Risk Conduct (CSR) by Apaza (2018) and the Parent-Adolescent Communication Scale (PAC)by Barnes and Olson (1982) adapted in Peru by Bueno, Tomas and Araujo (1998). Results: the resultsobtained show that there is no significant association between the level of communication with the fatherand risky sexual behaviors. On the other hand, it can be seen that the level of communication with themother is significantly associated with the age of sexual initiation (X2 = 2.303; p <.05), with the number ofsexual partners (X2 = 8.758; p <.01) and use of condoms (X2 = 3.803; p <.05) as a protection measure.Conclusions: the greater the communication, the lower the probability of risky sexual behavior.